The effect of inoculation by the drugs on the basis of the bacteria Mesorhizobium Ciceri on the chickpea productivity in the south of the Rostov region - G. V. Metlina; S. A. Vasilchenko; Yu. V. Laktionov; A. P. Kozhemyakov (Зерновое хозяйство России, 2018)
The effect of inoculation by the drugs on the basis of the bacteria Mesorhizobium Ciceri on the chickpea productivity in the south of the Rostov region For the zone of insufficient and unstable hydration of the Rostov region, the most promising leguminous crop is chickpea as it possesses high drought resistance, heat resistance, resistance to lodging and diseases. The research was conducted in 2015-2017 to determine the reaction of chickpea on the use of various strains of nodule bacterium Mesorhizobium cicero (producents of the inoculant ‘Risotorfin’). For the processing of chickpea seeds, there was used an inoculant, produced by the All-Russian Research Institute of Agricultural Microbiology (St. Petersburg). The research work was carried out on the fields of the agricultural scientific center ‘Donskoy’ (laboratory of cultivated crops technology), located in the southern soil and climatic zone of the Rostov region. The soil of the experimental plot is ordinary blackearth (chernozem), heavy loamy, calcareous on forestry loams. The object of research was the chickpea variety ‘Volgogradsky 10’, approved to use in the Rostov region. The article presents the study results of the influence of bio drugs on field germination, the preservation of plants for harvesting, the elements of the yield structure, the productivity, the economic and bioenergetic efficiency of chickpea cultivation. The greatest values of such elements of the structure of chickpea yield structure as ‘number of beans per plant’ and ‘number of seeds per plant’, ‘seed weight per plant’ and ‘1000-seed weight’ were obtained when using the biologic drug based on Mesorhizobium ciceri KZ-2013 . In the same version of the experiment, there was a maximum yield increase compared with the control variety and the highest indexes of energetic and economic efficiency of chickpea cultivation.